Diminished fertility in men with increased BMI - Najafi, Mohsen; Yousefi, Azin; C, Sharath Kumar; S, Malini S (Archives of Advances in Biosciences, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The incidence of obesity as a risk factor for normal life is increasing worldwide. Its impact on hypertension, cardiovascular diseases, osteoporosis, insulin resistance and diabetes mellitus, is well recognized. Previous studies have proved the association between female obesity and infertility and several linked genes have been worked out. However, a little is known about the effect of obesity on male reproductive system and infertility. Recently some clinical studies have reported diminished semen parameters like sperm count, sperm motility and vitality and changing in reproductive hormones in over weight and obese men. Lack of such study in Asian countries and particularly in Indian population who are genetically more prone to obesity necessitates picking up this research to achieve robust findings in this regard.